(untitled) (Літератури світу: поетика, ментальність і духовність, 2016)
The character in H. Pohutiak’s novel Severyn Nyklovs’ky is represented as a person who does his best to be incarnated in the image of real historical person Yan Shchasny Herburt changing into his look-alike for some time. Literary work «Magnate» («Magnat») in that part, which deals directly with the life and activity of the lordly man, is documental. The other plot line, which is connected to the life and activity of look-alike, is totally based on fiction and wild fantasy of H. Pohutiak. Here we can definitely speak about the imitation of biography or about quasi biography.